What is the ideal age of circumcision for wound healing time? - Aykac, Aykut; Yapici, Onur; Baran, Ozer; Oguz, Ural; Cakan, Murat (The European Research Journal, 2016)
Objective. Circumcision is practiced worldwide. Currently, the effect of age at the time of circumcision on wound healing is not fully known. This study aimed to determine the effect of age at the time of circumcision on wound healing. Methods. The study included 382 male patients aged ≤16 years that were circumcised between January 2014 and December 2014. Data for 345 patients that were followed-up regularly were evaluated retrospectively. Circumcision was performed using a bipolar diathermic knife. Circumcision wounds were considered healed when the 2 suture lines were observed to be completely apposed. Wound healing time was analyzed according to age at the time of circumcision. Results. Mean age of the patients was 7.2 years (range; 6 days-16 years). Mean duration of surgery was 327.5 sec and mean healing time was 4.3 days. The patients were classified according to age as group 1 (0-2 years; n=114; 32.9%), group 2 (3-6 years; n=60; 17.3%), and group 3 (7-16 years; n=171; 49.8%). Mean duration of surgery in groups 1-3 were 280.9 sec, 320.2 sec and 356.5 sec; respectively, and healing times were 4.1, 4.2 and 4.5 days; respectively. Healing time was significantly longer in group 3 than in groups 1 and 2 (p<0.05). There was no significant difference in healing time between groups 1 and 2 (p>0.05). Conclusion. Wound healing time was shorter in the patients aged 0-6 years than in those aged 7-16 years.